Systemic risk modeling with Lévy copulas - Yuhao Liu; Petar M. Djurić; Young Shin Kim; Svetlozar T. Račev; James Glimm (Journal of Risk and Financial Management, 2021)
We investigate a systemic risk measure known as CoVaR that represents the value-at-risk (VaR) of a financial system conditional on an institution being under distress. For characterizing and estimating CoVaR, we use the copula approach and introduce the normal tempered stable (NTS) copula based on the Lévy process. We also propose a novel backtesting method for CoVaR by a joint distribution correction. We test the proposed NTS model on the daily S&P 500 index and Dow Jones index with in-sample and out-of-sample tests. The results show that the NTS copula outperforms traditional copulas in the accuracy of both tail dependence and marginal processes modeling.
Keywords: 330; backtesting; CoVaR; Lévy process; NTS copula